THE ROLE OF L-ORNITHINE-L-ASPARTATE IN PROPHYLAXIS OF CYTOSTATIC-INDUCED LIVER INJURY IN PATIENTS WITH MULTIPLE MYELOMA - Maslova, G.S.; Skrypnyk, R.І.; Skrypnyk, I.N. (World of Medicine and Biology, 2021)
The paper presents the findings of our studies on the assessment of the effectiveness of L-ornithine-L-aspartate in the prophylactic of chemotherapy-induced liver injury in patients with multiple myeloma. 24 patients with multiple myeloma were examined (11 females and 13 males, ages 46–78). The condition assessment was conducted twice: before chemotherapy and after 3 courses of chemotherapy. Patients were analyzed for the following biochemical parameters: the activity of alanine and asparagine aminotransferases, gamma-glutamyltranspeptidase, alkaline phosphatase, total bilirubin, total protein, creatinine, urea, total blood calcium level. Depending on the inclusion of L-ornithine-L-aspartate as an adjuvant treatment, patients were divided into 2 groups: group I (n=12) – patients with multiple myeloma, who underwent only chemotherapy; group II (n=12) – patients with multiple myeloma, who during chemotherapy received L-ornithine-L-aspartate at a dose of 10 g/day intravenously for 10 days, then 5 g 2 twice a day for 20 days. Group ІІІ (n=20) the control group, included 20 practically healthy persons. It was established, that application of L-ornithine-L-aspartate as an adjuvant treatment in patients with multiple myeloma that undergo chemotherapy provides the effective prophylactic of pathological alterations in liver and kidney functional state.
Keywords: chemotherapy; hepatotoxicity; nephrotoxicity; adjuvant therapy